The splintering of Spain : cultural history and the Spanish Civil War, 1936-1939 - Ealham, Chris; Richards, Michael, 1961- (Cambridge University Press, 2005)
This book explores the ideas and culture surrounding the cataclysmic civil war that engulfed Spain from 1936 to 1939. It features specially commissioned articles from leading historians in Spain, Britain and the USA which examine the complex interaction of national and local factors, contributing to the shape and course of the war. They argue that the 'splintering of Spain' resulted from the myriad cultural cleavages of society in the 1930s. Thus, this book views the civil war less as a single great conflict between two easily identifiable sets of ideas, social classes or ways of life, than historians have previously done. The Spanish tragedy, at the level of everyday life, was shaped by many tensions, both those that were formally political and those that were to do with people's perceptions and understanding of the society around them.